"Cuban music is African music": negotiating Africa and the African diaspora on the world music stage - Whitmore, Aleysia K. (International Library of African Music, 2013)
Discussing the Senegalese band Orchestra Baobab's incorporation of Cuban music, guitarist and band member Latfi Benjeloune told me, "The music didn't come home and influence African music. Cuban music is already African. These are African sensibilities that are being expressed...in some ways we felt like parents with this music...it came from us” (Interview, 25 October 2011). Here, Benjeloune justifies his musical mixing by positioning himself in relation to the black Atlantic and African and Afro-diasporic peoples. Making musical and cultural connections across the black Atlantic is not a new phenomenon. African and Afro-diasporic musicians have long shared and taken up each other's musics, be it funk, jazz or rumba. The dynamics of musical mixing, however, have varied widely and have been affected by power relations, histories, cultural understandings and misunderstandings, as well as by access to technology, the workings of the music industry,and distribution networks.
Keywords: African Music